Explorando um modelo Agent Based-Stock Flow Consistent com inovação e firma agrícola - Barbant, Yasmim Dalila (2021)
Innovation is defined as the expression that designates changes in processes and products, with all the novelties implanted in the economic system, through research, development and investments, which end up increasing the efficiency of the production process through the improvement of products. Long-term innovations are relevant to a considerable expansion of total factor productivity in recent years, especially in the agricultural sector. To understand the long-term economic dynamics, an analytical tool can be constructed relating the general economic approach to the innovation process, integrating a Neo-Schumpeterian perspective with a post-Keynesian economic approach. Thus, this work aims to understand how the “endogenization” of technological cycle takes place, and its impacts, trying to build up a micromacrodynamics of the economy - which happens here not only at a theoretical level, but also with the formalization of a dynamic economic model. It is worth mentioning that the advances of Neo-Schumpeterian ideas were incorporated into KeynesianKaleckian models involving aggregate variables, based on the assumption that technological innovation generates expansive effects on productivity. These Keynesian-Kaleckian – or post-Keynesian – models can be classified as led by a key variable that generates additional demand – which increases investments and, consequently, profits, accelerating the accumulation process. Thus, a consistent stock flow methodology based on agents (or stock flow consistent-agent based model) is used to build a proxy model led by innovation in agriculture, seeking to incorporate recent agricultural innovations into a growth model with an export vector. The main result observed is the model itself, as well as its flow and stock matrices and the stylized facts of the model.